Five pillars for stakeholder analyses in sustainability transformations: The global case of phosphorus. Issue 107 (May 2020) - Lyon, Christopher; Cordell, Dana; Jacobs, Brent; Martin-Ortega, Julia; Marshall, Rachel; Camargo-Valero, Miller Alonso; Sherry, Erin
Highlights: Stakeholders hold complex roles, capacities, power. Stakeholders can be read as complex entities within complex social-ecological systems. Deeper reading of stakeholders is important for identifying leveragers for sustainability transformations. Abstract: Phosphorus is a critical agricultural nutrient and a major pollutant in waterbodies due to inefficient use. In the form of rock phosphate it is a finite global commodity vulnerable to price shocks and sourcing challenges. Transforming toward sustainable phosphorus management involves local to global stakeholders. Conventional readings of stakeholders may not reflect system complexity leaving it difficult to see stakeholder roles in transformations. We attempt to remedy this issue with a novel stakeholder analysis method based on five qualitative pillars: stakeholder agency, system roles, power and influence, alignment to the problem, and transformational potential. We argue that our approach suits case studies of individual stakeholders, stakeholder groups, and organisations with relationships to sustainability challenges.